Characteristics of Innovations in the Cultivation Process of Intensive Red Chili - Wardah, Eva; Budi, Setia (Journal of Tropical Horticulture, 2019)
The characteristics of innovation and the process of implementing intensive red chili cultivation need to get training from parties involved in intensive red chili cultivation activities. The purpose of this study is to determine farmers' assessment of the innovation characteristics of intensive red chili cultivation. The research sample consisted of 32 red chili farmers in Meurah Dua District, Pidie Jaya Regency, Indonesia. This research was conducted through a qualitative descriptive approach with data measurement using a Likert scale. Based on farmers' responses to the innovation characteristics of intensive red chili cultivation, the results sequentially showed that the cultivation (1) having a relative profit level, (2) easy to try, (3) suitability level, (4) observable, and (5) level of innovation complexity. The process of red chili cultivation activities include; (1) seed procurement and seeding, (2) land management, (3) planting, (4) plant maintenance, (5) pest and disease control, and (6) harvesting. The role of agricultural extension is needed to continue to provide training and assistance to address problems faced by intensive red chili farmers especiallyin the selection of superior seeds and good seeding process, balanced fertilization, integrated pest and disease control.